Implementasi Algoritma Multiply With Carry Generator (MWCG) dalam Pengacakan Soal Ujian Semester Berbasis Web pada SMKN 1 Kendari - Rizal Adi Saputra; Iklil Awalda Tariza; Bambang Pramono (Teknik Informatika Universitas Pamulang, 2022)
A semester exam conducted using google form on SMK 1 Kendari could be used as a loophole for cheating. It is requires a system that can randomize the question using specified algorithm. Multiply With Carry Generator algorithm is a simple interlinear numbers algorithm that can be used to solve this problem. In several previous studies, this algorithm has been widely used to generate random numbers in several programming applications. They are outgrown by the algorithm Multiply With Carry Generator, which is at the speed of generating random numbers and also the length of the randomness cycle produced by Multiply With Carry Generator, which uses two seeds to produce more seed variations. Based on testing runs perform to test the randomize of the algorithm Multiply With Carry Generator in 10 students with 20 numbers of question produce randomize question with test results received . It’s prove that Multiply With Carry Generator algorithm can be used to randomize the question and can be implemented in SMK 1 Kendari exam test system.